The roles of shame and guilt in criminal behavior: The case study of shiraz youth - azadeh dehghanfar; amir paknahad; amir irvanian (مجله علوم روانشناختی, 2023)
Background: According to psychological research, committing a crime is one of the most important topics in criminology research, and in this context, individual emotions play a significant role. The feeling of shame and guilt is one of the most important personal feelings, yet it has received little attention in the research that has been conducted. Studying young people's behavior regarding shame and guilt is especially important since they play a critical role in every society. Aims: This study aimed to examine the role that shame and guilt play in committing crimes by young people. Methods: This study is a survey study. This study is based on the statistical population of all the youth of Shiraz, specifically 300 youth of 18 to 35 years of age selected by random selection and surveyed using a questionnaire designed by the researchers. The data were analyzed using Pearson's correlation coefficient, chi-square, and regression. Results: The correlation coefficient between shame and crime was negative and statistically significant (p<0.01). Consequently, an increase in shame leads to a decrease in crime. Further, the calculations show that guilt and committing a crime are negatively and significantly correlated (p<0.01), and that guilt increases as a crime decreases. According to the regression results, there is more evidence that shame plays a greater role in committing a crime than guilt. Conclusion: Shame and guilt play a significant role in deterring young people from committing crimes. It is possible to reduce youth crime by strengthening these feelings in young people in various ways. It is important to note that emphasizing shame should take precedence over highlighting guilt